Reformulation of Expert Qualifications in the Indonesian Criminal Justice System (A Comparative Study between Indonesia, the United States, the United Kingdom, and Australia) - Attidhira, Safira Widya (Universitas Islam Sultan Agung, 2024)
This research aims to compare the regulations regarding experts in advanced countries such as the United States, the United Kingdom, and Australia, to then be used as examples for reformulating expert standardization in Indonesia. This study employs a normative juridical method using secondary data consisting of primary legal materials related to experts and secondary legal materials, such as international journals and books. The approach used in this research includes conceptual, legislative, and comparative approaches with other countries. The results of the study show that the United Kingdom has Civil Procedure Rules that extensively regulate the rights and obligations of experts, while the United States has the Federal Rules of Evidence, which also specifically regulate the qualification standards for experts. In Australia, regulations related to experts have been established in the Evidence Act 1995 and Federal Court Rules 2011, which often discuss the code of conduct for experts in court. This research concludes that Indonesia needs to adopt more detailed regulations regarding experts in the criminal justice system, starting with the creation of a code of conduct containing requirements to become an expert, the rights and obligations of experts, and the mechanism for the process of providing expert witness testimony. However, it is not sufficient to stop there; there must be encouragement from the authorities to ensure that this code of conduct is read and understood by prospective experts. Additionally, there should be standards for qualifications, experience, and the mechanism for providing testimony due to the lack of credibility and reliability of an expert presented in court.